2021
DOI: 10.7759/cureus.20468
|View full text |Cite
|
Sign up to set email alerts
|

Arabic Translation and Linguistic Validation of the SCAR-Q Scale Module

Abstract: Scars are a fairly common complaint in the clinical setting; they can arise from trauma, burns, or after surgical procedures. They can have a detrimental impact on the quality of life of patients. A well-established method of quantifying such an impact is through patient-reported outcome measures (PROM). SCAR-Q is a relatively new and robust questionnaire that was developed and validated by McMaster University. Our study aims to translate SCAR-Q to Arabic. SCAR-Q has a holistic approach to scars and does not t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…One study suggested that SCAR‐Q is the first and only validated scar assessment for all scar types 2 . Two studies validated the SCAR‐Q questionnaire in French and Arabic as well 49,50 …”
Section: Resultsmentioning
confidence: 99%
“…One study suggested that SCAR‐Q is the first and only validated scar assessment for all scar types 2 . Two studies validated the SCAR‐Q questionnaire in French and Arabic as well 49,50 …”
Section: Resultsmentioning
confidence: 99%
“…With an increasing focus on quality of life, it becomes essential to employ linguistically validated tools for assessing patients and delivering enhanced care. Patient-reported outcome (PRO) instruments like SCAR-Q facilitate result evaluation during follow-up visits, making them integral to the overall treatment process and not to be overlooked [22].…”
Section: Discussionmentioning
confidence: 99%
“…The SCAR-Q has been translated in twelve languages, and validated in the French, Arabic, and Italian language [23][24][25]. The French and Arabic study investigated adults.…”
Section: Discussionmentioning
confidence: 99%